NURSES’ KNOWLEDGE WITH THE EFFORT OF PREVENTION OF NOSOCOMIAL INFECTION (Study at Inpatient Unit Regional Hospital Dr. Sayidiman Magetan) - Eka Nugraheni S; Arif Wijaya; Yunan Yusuf Habibi (STIKES Insan Cendekia Medika Jombang, 2014)
Hospital patient safety is a system where hospitals make patient care safer and prevent injuries caused byfaults due to carry out an action or not take action that should be taken. This could happen due to a lack ofknowledge of nurses about the concept of prevention of nosocomial infection. The purpose of this study wasto know the relationship of nurses’ knowledge with the effort of prevention of nosocomial infections atinpatient unit Regional hospital Dr. Sayidiman Magetan.The study method used was Cross SectionalAnalytic. The researcher conducted measurement or research in one period. Population was as many as 59nurses. Sample taken was all nurses as many as 59 people. Technique used in this study was total samplingtechnique. Data collection of respondent used a questionnaire. Independent variable was nurse’s knowledgeabout nosocomial infection and dependent variable was prevention effort of nosocomial infection. Dataprocessing used editing, coding, scoring, tabulating and correlational test of pearson.The study result of 59respondents of nurse’s knowledge about prevention of nosocomial infection had correlation coefficient withthe prevention of nosocomial infection with a significant value of p-value = 0,025 < 0,05 where the value of r= 0,293, which means anyrelationship of nurse's knowledge with prevention of nosocomial infection. Theconclusion of this study, nurses with the knowledge of prevention of nosocomial infections in normaldistribution.Keywords: Knowledge, Nurse,Nosocomial Infection